Juridical Overview of The Financing of MSME Micro Capital Service Unit (ULaMM) Syariah - Nurhikma Nurhikma; Ulya Atsani; Kieren Akbar (JURIS (Jurnal Ilmiah Syariah), 2021)
This article is motivated by the special tasks carried out by thePT. Madani National Capital (PNM), which is only to carry out business activities to channel funds without making efforts to raise funds because this business unit is not a banking institution. The Micro Capital Service Unit (ULaMM) is a capital loan service for micro and small businesses accompanied by guidance to develop their business.UlaMM has been running business activities and providing financing services for the development of cooperatives, micro, small and medium enterprises. The agreement made by both parties was made in writing in accordance with POJK Number 16/POJK.05/2019 concerning the Supervision of PT. Permodalan Nasional Madani, Micro Capital Service Unit (ULaMM). This research uses descriptive qualitative method with data analysis used with descriptive analysis. Based on the method that has been used, it can be concluded that the agreement made is stated in writing in an agreement, this is in line with the provisions contained in POJK article 7 paragraph (2) which regulates that the financing service agreement must be made in writing. The agreement made is also in accordance with the provisions contained in Article 1320 of the Civil Code which regulates the legal terms of agreement.